Antonia de Mendoza, queen's lady-in-waiting, countess of Benavente and poet of the XVII century - Marín Pina, M.ª Carmen (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Antonia de Mendoza (¿?-Madrid 1656), countess of Benavente per her marriage to Juan Francisco Alfonso Pimentel de León, X conde de Benavente, wrote verses that barely reached the printing. Some of those are collected in a handwritten volume of Poesías varias with the work of other amateur poets of the time. The objective of this article is to revise the figure and work of the countess of Benavente in the context of the courts of the Queens Isabel de Borbón and Mariana de Austria, to whom she served as lady-in-waiting, study her relationships with the nobles, among them the III marquis of Velada, and reconsider the attribution of various poems.
Keywords: Antonia de Mendoza; III marquis of Velada; queen´s lady-in-waiting; motes; handwritten poetry